Intersections Around Ambivalent Sexism: Internalized Homonegativity, Resistance to Heteronormativity and Other Correlates - López-Sáez, Miguel Ángel; García-Dauder, Dau; Montero, Ignacio (Frontiers in Psychology, 2020)
This article explores the connections between the construct of sexism and other sociodemographic and attitudinal variables, such as internalized homonegativity and heteronormative resistances, among psychology students. Both unrefined and inferential analyses were used with a representative sample of 841 psychology students from public universities in Madrid. Results showed higher levels of sexism, internalized homonegativity and low resistances to heteronormativity among groups of men, heterosexuals and conservatives. Interactions were found that showed a higher degree of hostile sexism in: heterosexual people with respect to LGB and heterosexual men with respect to heterosexual women. Also, interactions were found to show a greater degree of heteronormative resistance in: LGB people with respect to heterosexuals and left-wing women with respect to right-wing women. Correlations with sexism varied according to gender identity and sexual orientation. In addition, heteronormative resistances correlated negatively with sexism, while some components of internalized homonegativity correlated positively. Political affiliation was the most frequent predictor of sexism. The results highlight the need for an intersectional approach to understanding the phenomenon of sexism.